AKTIVITAS ENZYM SELULASE YANG DIHASILKAN OLEH BAKTERI Serratia marcescens PADA SUBSTRAT JERAMI - Khrisna Lazuardi Budi; W Wijanarka; Endang Kusdiyantini (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2018)
Cellulose (EC 3.2.1.4) is enzyme complex consisting of some enzymes which together decomposing cellulose into glucose by hydrolizes the β-1,4 bond in cellulose. The purpose of this study is to determine cellulose activity which produced by Serratia marcescens in different substrate concentration and at the time of incubation T4, T8, T12. This research uses Randomized Block Design (RBD) factorial pattern with two factors. The first factor was variation of straw substrate which had been delignificated (V0, V1, V2, V3). The second factor is the variation of time incubation (T4, T8, T12). Each factor is repeated 3 times. The data obtained were analyzed using Analysis of Variance (ANOVA) (α = 0.05). The result shown that variation concentration of straw, and the interaction (combination) between the straw substrate and the incubation time substrate was not significantly different. The result treatment of incubation time was significantly different of the cellulase activity. The result of anova analyzed is obtained that F count(α = 0.05) value from straw substrate, interaction (combination) between the straw substrate and the incubation time substrate, and incubation time was 0.53; 2.18; 8.00. F table(α = 0.05) value of straw substrate, interaction (combination) between the straw substrate and the incubation time substrate, and incubation time was 2.99; 2.20; 3.39. The result of anova, is continued by BNT 5% test. The result of BNT test shown that the highest incubation time of cellulase activity was in incubation time 12 hours with the average value 0.26 U/mL. Key Word : cellulose, Serratia marcescens, straw substrate, incubation time